Pengaruh Kompensasi Dan Lingkungan Kerja Pada Loyalitas Karyawan Berdasarkan Jenis Kelamin - Stephani, Lea Ayu; Wibawa, I Made Artha (E-Jurnal Manajemen, 2014)
This study aimed to examine the effect of compensation and work environment on employee loyalty by gender either simultaneously or partially.73 Respondnts as employees is determined using the method of saturated samples. Data were obtained through questionnaires,were analyzed using discriminant analysis techniques (discriminant analysis). Based on the analysis it was found that compensation and work environment simultaneously significant effect on employee loyalty. Partially compensated significant effect on employee loyalty. The working environment is partially no significant effect on employee loyalty. Keywords: Compensation, Employee Loyalty, Gender and Work Environment
Keywords: Compensation, Employee Loyalty, Gender and Work Environment